Musical morphogenesis - a self-organizing system - Oliveira, M. J. DE; Sousa, J. P.; Costa, V. C.; Oliveira, S. M.; Mena, A. (Kine[SIS]tem - From Nature to Architectural Matter Conference Proceedings, 2017)
We feel and seize the built environment through senses and body’s interactive movement. During this process, our mind and physical status is processing solutions and methods of integration and adaptation that enable us to integrate and live with and in our surrounding environment. In this paper, we provide an overview on “Musical Morphogenesis” interactive installation, which interacts through colour, light, movement and sound with the environment and its inhabitants. In addition, we intend to take visitors in a sensorial journey to explore the dynamic action of a network of genes during the development of an organism. Finding its roots in the Autopoiesis’ theory (Maturana & Varela 1980), “Musical Morphogenesis” acts and interacts as a self-producing system. This installation results from a multidisciplinary collaboration of six main scientific disciplines: complex systems, computational biology, music, architecture, robotics, and science communication. During the design and implementation of the installation’s components, the specificities of each discipline had to be taken into consideration, resulting in an extremely challenging project.